Perambulation notes of the commissioner of agriculture 2002-2004 - Kannan, R. (Chennai, 2004)
These Notes of Perambulation (Inspection) relate to the worst drought year 2002-2003 and the difficult year of 2003-2004. It is important to document the experience of this period. since some time in the future when times and the persona change.
Keywords: Agriculture